Critical Speculations In AI Design: Ethical Narratives And Visual Experiments In Post-Human Aesthetic Practices - Sultana, Marufa; Sugiarto, Sugiarto (International Journal of Graphic Design, 2025)
The rapid integration of Artificial Intelligence (AI) into design practice presents both opportunities and ethical dilemmas, particularly within the expanding field of speculative design. Current design discourses often emphasize utility and innovation while overlooking the complex ethical narratives and aesthetic shifts emerging in post-human interactions. This study aims to explore how speculative design can utilize AI not merely as a tool, but as a collaborator in reimagining human-machine relationships through visual and conceptual experimentation. Employing a qualitative visual methodology that combines experimental design practices, critical design theory, and post-human ethics, the research analyzes a series of AI-generated visual experiments that interrogate identity, agency, and authorship. Key findings reveal that AI-driven speculative visuals challenge anthropocentric norms, foster ethical ambiguity, and introduce new aesthetic vocabularies that disrupt conventional design logic. The output includes a set of visual compositions that function as critical artefacts, questioning the future of design ethics and post-human subjectivity. This study concludes that integrating AI into speculative design opens space for designers to act not as problem-solvers but as ethical provocateurs, expanding the boundaries of visual culture and design agency in an era of machine intelligence. These findings contribute to ongoing debates in design theory and offer conceptual and methodological tools for rethinking ethical frameworks in contemporary visual practice.